Contribuição ao estudo do conversor multinível híbrido em cascata monofásico empregado na interface entre fonte fotovoltaica, banco de baterias e rede elétrica. - Gamba, Cindy Jireth Ortiz (2017)
This master thesis presents an energy management strategy in order to eliminate power fluctuations from a photovoltaic source through a single-phase cascade hybrid multilevel grid-tie converter associated with a battery energy storage system. The converter consists of two full bridge cells connected in series, controlled by a hybrid modulation strategy. The cell connected to the photovoltaic source (main cell) operates with single pulse modulation in the fundamental frequency, to regulate the voltage of its DC link by controlling the trigger angle of the switches, in order to transfer the maximum power available to the power grid keeping the dc link constant. The cell connected by the battery bank (auxiliary converter) operates with high frequency PWM modulation, providing dynamic response capacity fast enough to compensate for both power fluctuations and harmonic distortion produced by the main cell by regulating the current injected into the grid as established by Standards (ABNT NBR 16149, 2013; 16150, 2013; IEC 62116, 2012). This is done through the use of a current regulator based on the proportional resonant compensator with a harmonic compensating bank. Simulation results obtained with the hardware-in-the-loop Typhoon HIL402 platform prove the theoretical analysis and the feasibility of the proposed system.